Biopolymers as alternatives to synthetic polymers in flame‐retarded polymeric composites: A study of fire and mechanical behaviors. Issue 1 (17th October 2022) - Teles, Fernando; Antunes, Filipe
Abstract: The impact of polymeric materials on the environment is a growing concern and an incentive for their commercial appeal. In composites, the trend is to replace matrices of synthetic polymers (SPs) with biopolymers (BPs) to develop bio‐based composites. The increasing demand for such materials has driven their research and application in many industrial sectors, often accompanied by increasingly restrictive fire safety regulations. With the aim of decreasing the flammability of composites, various approaches have been pursued, in particular the use of flame‐retardant (FR) additives. However, at high FR loads, the mechanical properties can be compromised. This article briefly overviews some aspects of the fire behavior and mechanical properties of BPs and bio‐based composites. Using a chart‐based framework and quadrant‐based quantitative analysis, the fire and mechanical properties of flame‐retarded composite formulations are evaluated simultaneously, aimed at comparing the effects of BPs and SPs in flame‐retarded polymeric composites in relation with other variables. Abstract : Bare biopolymers ( left side ) can burn vigorously under a flame, with production of char, volatiles and smoke. When a suitable flame retardant is added ( right side ), the amount of generated char increases, thus creating a barrier effect that slows down the flame and decreases the amount of volatiles and smoke produced.